2012
DOI: 10.1016/j.eats.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Popliteomeniscal Fascicle Tear: Diagnosis and Operative Technique

Abstract: The occurrence and the consistency of the popliteomeniscal fascicle between the popliteus tendon and the lateral meniscus have been the subject of debate. It is difficult to diagnose and treat popliteomeniscal fascicle tears. Furthermore, popliteomeniscal fascicle tears are difficult to identify with arthroscopy. This article describes the diagnostic factors for popliteomeniscal fascicle tears and the safe, effective operative techniques that can be used for their treatment. We suggest that popliteomeniscal fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 11 publications
(17 reference statements)
1
36
0
2
Order By: Relevance
“…Only T1ρ showed significance and the T2 values showed a similar trend but no significance, probably because T1ρ values have higher sensitivity to detect compositional cartilage matrix changes after ACL injury [14,16,17]. Similar to our study, Shin et al [10] found osteochondral lesions in the posterior area of the lateral femoral condyle during arthroscopic evaluation of subjects with popliteomeniscal fascicle tears. They believed that the cause of osteochondral lesions was the repetitive entrapment of the lateral meniscus caused by posterolateral translation in a situation where a popliteomeniscal fascicle tear occurs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Only T1ρ showed significance and the T2 values showed a similar trend but no significance, probably because T1ρ values have higher sensitivity to detect compositional cartilage matrix changes after ACL injury [14,16,17]. Similar to our study, Shin et al [10] found osteochondral lesions in the posterior area of the lateral femoral condyle during arthroscopic evaluation of subjects with popliteomeniscal fascicle tears. They believed that the cause of osteochondral lesions was the repetitive entrapment of the lateral meniscus caused by posterolateral translation in a situation where a popliteomeniscal fascicle tear occurs.…”
Section: Discussionsupporting
confidence: 76%
“…Without proper diagnosis and treatment, popliteomeniscal fascicle tear (PMFT) can lead to continued instability of the lateral meniscus increasing the risk of developing complex meniscal tear and articular cartilage damage [10].…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de los avances en el conocimiento de este tipo de lesiones, la evaluación mediante artroscopia sigue siendoen la actualidad el gold standard para el diagnóstico de certeza, puesto que permite una visualización directa de los fascículos poplíteo-meniscales y la evaluación de la movilidad del menisco lateral. 13 Existen múltiples técnicas quirúrgicas publicadas para el tratamiento de este tipo de patología: meniscectomía, 14 reduccióntérmica meniscal, 15,16 reparación con sutura meniscal en forma abierta 9 y artroscópica, 17,18 además reconstrucción de fascículos poplíteomeniscales con utilización de injerto. 1 Dado lo poco frecuente del Síndrome de Menisco Hipermóvil, el propósito de esta publicación es describir nuestra experiencia en el diagnóstico y tratamiento de este tipo de lesiones dentro de un grupo de traumatólogos especialistas en rodilla, en relación a 9 casos clínicos.…”
Section: Introductionunclassified
“…Without proper diagnosis and treatment, popliteomeniscal fascicle tears can lead to continued disability, complex tears of the lateral meniscus, which are often irreparable, and chondral lesions because of the large mobile fragment. 4 The popliteomeniscal fascicles are composed of 3 dis-tinct fasciculi, anteroinferior, posterosuperior, and posteroinferior, that attach to the lateral meniscus at the popliteal hiatus (Figure 1). 5 Sussmann et al 6 suggested that, embryologically, the fascicles allow vascular supply to the lateral meniscus.…”
mentioning
confidence: 99%
“…Thompson et al 8 reported that less than half of the lateral meniscus shows mobility when the popliteomeniscal fascicles are intact. Shin et al 4 proposed that when more than half of the lateral meniscus shows mobility, a popliteomeniscal fascicle tear should be suspected.…”
mentioning
confidence: 99%